2015
DOI: 10.1093/mnras/stv100
|View full text |Cite
|
Sign up to set email alerts
|

BUDHIES II: a phase-space view of H i gas stripping and star formation quenching in cluster galaxies

Abstract: We investigate the effect of ram-pressure from the intracluster medium on the stripping of HI gas in galaxies in a massive, relaxed, X-ray bright, galaxy cluster at z = 0.2 from the Blind Ultra Deep HI Environmental Survey (BUDHIES). We use cosmological simulations, and velocity vs. position phase-space diagrams to infer the orbital histories of the cluster galaxies. In particular, we embed a simple analytical description of ram-pressure stripping in the simulations to identify the regions in phase-space where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
314
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 242 publications
(337 citation statements)
references
References 82 publications
19
314
2
2
Order By: Relevance
“…A similar plot was already shown in Jaffé et al (2015) but it is presented here again with the much larger spectroscopic sample. A few areas, defined in Jaffé et al (2015), are shown. The 'recent infall' and 'virialized' areas reflect the orbital histories of cluster galaxies, as already discussed in Section 3.1.…”
Section: Distribution Of Red Blue and Hi -Rich Galaxiessupporting
confidence: 80%
See 3 more Smart Citations
“…A similar plot was already shown in Jaffé et al (2015) but it is presented here again with the much larger spectroscopic sample. A few areas, defined in Jaffé et al (2015), are shown. The 'recent infall' and 'virialized' areas reflect the orbital histories of cluster galaxies, as already discussed in Section 3.1.…”
Section: Distribution Of Red Blue and Hi -Rich Galaxiessupporting
confidence: 80%
“…It is possible that some of these (especially the most massive ones) have been 'mass quenched' (by internal processes such as AGN feedback; see Peng et al 2010), but additional 'environmental quenching' might also be at play, especially for lower mass galaxies. As discussed in Jaffé et al (2015), the abundance of passive galaxies in the cluster outskirts cannot easily be explained by RPS alone (or backsplashing galaxies). However, a more plausible explanation for this effect is that many of these galaxies started to be quenched in a previous environment.…”
Section: Distribution Of Red Blue and Hi -Rich Galaxiesmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the rather extreme conditions within the gravitational potential of a galaxy cluster can work in the opposite direction as well. The ram pressure from the intracluster medium (ICM) is probably able to strip or evaporate the cold gas reservoir of galaxies (Gunn & Gott 1972;Cowie & Songaila 1977;Giovanelli & Haynes 1985;Chung et al 2009;Jaffé et al 2015) and can strongly affect the fueling of the AGN. Other studies, however, have argued that ram pressure stripping cannot be as effective in transforming blue-sequence galaxies to red (e.g.…”
Section: Introductionmentioning
confidence: 99%